Performance and development trends of ultrasound diagnostic systems in military settings: a review - Lu, Chang; Huang, He-Jing (The Ultrasound Journal, 2025)
With the evolving challenges of modern warfare, battlefield medical support systems are often required to enhance capabilities in rapid response, flexible deployment, and modular integration. Ultrasound diagnostic systems, appreciated for their portability and ability to provide real-time imaging without ionizing radiation, have been investigated for potential use in early injury screening and rapid assessment in combat and pre-hospital settings. This review provides an overview of representative battlefield-adapted ultrasound systems, such as the Sonosite M-Turbo, Edge II, and GE Vscan Extend, and discusses their reported limitations, including issues with deployment reliability, image quality, operational complexity, and telecommunication capability. Emerging technological directions are explored, including artificial intelligence-assisted diagnosis, multimodal integration, adaptation to extreme environments, and integration with unmanned platforms. Furthermore, a conceptual framework is proposed, focusing on areas such as research and development, standardization, deployment at combat nodes, and training infrastructure, which may contribute to future advancements. The goal is to provide insights that could guide the future development and strategic planning of next-generation tactical medical imaging systems.